Online Professional Development for Improving Teacher's STEM PCK Competence, Can It Be An Alternative? (An Evaluation Using the CIPP Model) - Santi Setiani Hasanah*; Anna Permanasari; Riandi Riandi (JIPI (Jurnal IPA dan Pembelajaran IPA), 2021)
During the pandemic, face-to-face training should not be carried out to reduce the spread of the covid outbreak. Therefore, online teacher professional development is an alternative method to replace the face-to-face training. In a program implementation, evaluation is an important component to determine whether the program has been implemented well or not. This evaluation is important to determine the effect of this online training on improving STEM PCK teachers. The evaluation used the CIPP model (Context, Input, Process, and Product), with the embedded mixed method research. This research was conducted on 60 science teachers of SMP alumni online training organized by PPPPTK IPA, from the “Sayangi Bumi” classroom. The results of the context evaluation show that 100% of respondents stated that the program is in accordance with the needs of teachers to strengthen their PCK., while the resources used in the program (Input evaluation) were good. The program implementation process ran 100% as planned and the product evaluation shows an increased teachers' understanding of the STEM approach. Teacher considered that the online professional development is very useful for teachers and can develop their skills in implementing STEM learning during distance learning. Online PD, apart from low-cost, can actually be an alternative way in improving teachers' STEM PCK competence and it also can reach all islands in Indonesia